Doença de chagas aguda: o impacto da transmissão oral no estado do Pará - RODRIGUES, Aline Danielle Di Paula Silva (2023)
The article aims to analyze the oral transmission of Acute Chagas Disease in the state of Pará Brazil. This is a retrospective, quantitative and analytical study, which evaluated the cases notified during the years 2007 and 2019 in the state of Pará. Data referring to the municipality of residence, sex, race/color, age group, place of residence were considered. infection, zone of infection, month and year of the first symptom of Chagas disease. A total of 1898 cases were reported during the period analyzed, with an average of 146.00±84.61 notifications per year. The Intermediate Geographic Region of Belém concentrated the largest number of cases (59.69%), but it was the region of Breves that had the highest incidence rate (118 cases/100 thousand inhabitants). The sociodemographic profile was characterized by individuals of mixed race/color, between 20 and 59 years old, infected in their place of residence, but there was no statistically significant difference (p value < 0.05) between males and females, nor between the areas of urban and rural residence. The seasonality of Chagas disease showed that the months from July to December concentrated the majority of cases (76.24%), however, there was a statistically significant difference (p value <0.05) only in the number of incident cases between the months of August to November. Finally, it was estimated that if the occurrence of cases maintains this pattern in the coming years, in 2030 there will be approximately 500.40 cases/year. The findings in this study were essential and can be used as tools for the development of new actions and public policies for the prevention of the disease in the state in an effective, timely and targeted manner.